(untitled) (Medicine Today, 2018)
Low serum vitamin D levels have been associated with various vascular diseases. Very little is known its association with acute stroke in Bangladeshi population. We therefore sought to assess whether low serum 25- hydroxyvitamin D, a marker of vitamin D status is associated with acute stroke. We performed a prospective study in Comilla Medical Collage, Comilla, from November 2016 to November 2017. All the patients diagnosed as acute ischemic stroke on the basis of CT scan or MRI of brain. Patients were eligible for inclusion if they were admitted with onset of symptoms within 24 hours. Estimation of 25(OH)D level was done at presentation. The patients were stratified by vitamin D status, >30 as vitamin D sufficient, vitamin D 20-20.9 as insufficient and finally vitamin D<20 as deficient. Multivariate logistic regression analysis revealed that out of the desired 7 variables, smoking, hypertension and low serum vitamin D were found independent predictors for acute stroke with ORs being 1.44, 4.23 and 2.39 respectively. Vitamin D deficiency represents an important risk factor for acute stroke and it might play a causal role in the development adverse events associated with stroke. Medicine Today 2018 Vol.30(1): 34-37